ANALISIS PENERAPAN STUDI SOSIOTEKNIS PADA KEPUASAN KONSUMEN HOTEL ASOKA LUXURY BANDAR LAMPUNG - Andy Dharma Tilaar (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2017)
One of the internal control structure adopted by the company is the controlling structure of theworkforce. Pengendalaian labor in hotel operations determine the success Hotel. The success of thehotel one of which is a success in the field of service. The success in the field of service can provide apositive effect on profit hotel revenue. The review provides an overview reviewing authors in thehospitality industry in suss out the problem in the field of efficiency or effectiveness of work in the hotelthat became a trend for Visit Lampung today.Implementation Study on Consumer Satisfaction with socio-technical variables on ASOKALUXURY, and is expected to have a positive impact which is expected to become a new studyconducted selanjutnya.Setelah data analysis is the conclusion of this study as follows from thecalculation, there is increased gradually from the application of the approach socio-technical evenlyprice increase completion of work at 0:16 every day, which means socio-technical approach provides apositive impact on the group of employees who menggunakannya.Dari described results it can beconcluded that the application of the model of studies socio-technical a positive impact on improvingservices at Hotel ASOKA LUXURY